Assessing vulnerability and framing adaptive options of two Mediterranean wine growing regions facing climate change: Roussillon (France) and McLaren Vale (Australia) - Anne-Laure Lereboullet; Douglas Bardsley; Gérard Beltrando (EchoGéo)
An increase in temperatures and a decrease in precipitations could be prejudicial to maintaining a premium wine production in regions with a Mediterranean climate. The present article offers to assess recent and future exposure to such changes in two Mediterranean wine producing regions: Roussillon (France) and McLaren Vale (Australia); as well as to frame elements increasing their vulnerability to such changes, and reversely elements that could help increase their adaptive capacity. A study of temperature and rainfall data observed (1956-2010) in Perpignan and Adelaide and simulated (2001-2060) by ARPEGE-RETIC-V4 and CSIRO Mk3.5 was completed by sixty-one interviews with key stakeholders of the wine industry in both regions. Results show that producers had to face an increase in temperature and a decrease in rainfall in the last decade, and this tendency, according to climate models, is likely to continue through to 2060, with a fair level of uncertainty. This has negative impacts on grape maturation, and traditional vineyard management may not be sufficient to deal with it in the long term. Implementing new strategies of adaptation to uncertainty in climate, as well as in economy, depends on: a sufficient financial capital, a sustainable management of water resources, and flexibility in legislation. To achieve this, diversification and entrepreneurship of producers is particularly important.